Educating film-makers : past, present and future - Petrie, Duncan J., 1963-; Stoneman, Rod (Intellect, 2014)
A timely consideration of both the history and the current challenges facing practice-based film training, Educating Film-Makers is the first book to examine the history, impact, and significance of film education in Britain, Europe, and the United States.